Pyrene-tagged poly(N-vinyl pyrrolidone) as efficient nano-carrier for anticancer drug delivery - Mitra K.; Maity S.; Hajra A.; Singh S.; Mondal S.; Singh J.; Maiti P.; Ray B. (My University, 2025)
Herein, we report the use of self-assembled amphiphilic pyrene-tagged poly(N-vinyl pyrrolidone) (PyPNVP) micelles as effective anticancer delivery vehicle. Self-assembly phenomenon of PyPNVP has been studied in aqueous medium. Anticancer drug doxorubicin has been encapsulated in the hydrophobic micellar core and in vitro release profiles have been explored in four different pH values (pH 7.4 − 1.4). The drug-loaded construct has shown pH-responsive higher drug release at lower pH. Anticancer activity of the construct has been studied against human squamous cell carcinoma of the cervix uteri cell line. The in vitro study has shown the highly effective tumoricidal activity. © 2023 Taylor & Francis Group, LLC.